2020 Update to Spinal Muscular Atrophy Management in Saudi Arabia - Bashiri, Fahad A.; Temsah, Mohamad-Hani; Hundallah, Khalid; Alsohime, Fahad; AlRuthia, Yazed (Frontiers in Pediatrics, 2021)
Novel therapeutic strategies have shown some promise in treating spinal muscular atrophy (SMA). However, the outcomes and acceptance of these new strategies are yet to be explored. We aimed to investigate physicians' opinions and perceptions towards management strategies of SMA across Saudi Arabia. This is a cross-sectional survey using a self-administered, structured questionnaire sent to physicians who care for SMA patients during the Saudi Pediatric Neurology Society Conference's annual conference. A total of 72 clinicians of different neurological subspecialties were included. 48.6% prescribed nusinersen to their patients, with 39% of them having patients started on nusinersen. Though, 8.3% prescribed onasemnogene abeparvovec for 1-3 patients, while none of their patients started on the treatment. 64.3% stated that the only treatment available for SMA in their settings is supportive care. Around 69.4% described having a moderate to high knowledge on SMA gene therapy, and 79.2% would recommend it. 48.6% confirmed they would prescribe gene therapy at the age of 6 months, and 78.3% would prescribe it for type-I SMA. Pediatric neurologists are receptive to novel and innovative therapies for SMA in Saudi Arabia. However, the high treatment acquisition cost, strict regulations, logistical issues, and budget constraints delay their adoption and implementation.